Data for Effective antireflection and surface passivation of silicon using a SiO2/a-TiOx film stack - Bonilla, R; Wilshaw, P (University of Oxford, 2017)
This data describes the capacitance-voltage, conductance-voltage, lifetime, and surface potential measurements of silicon samples used in this study. All data is embedded in Matlab figures with .fig format.